Reliability and utility of the Behaviour Support Plan Quality Evaluation tool (BSP‐QEII) for auditing and quality development in services for adults with intellectual disability and challenging behaviour. (30th July 2012) - McVilly, K.; Webber, L.; Paris, M.; Sharp, G.
Abstract Background Having an objective means of evaluating the quality of behaviour support plans (BSPs) could assist service providers and statutory authorities to monitor and improve the quality of support provided to people with intellectual disability (ID) who exhibit challenging behaviour. The Behaviour Support Plan Quality Evaluation Guide II (BSP‐QEII) was developed to monitor and assess BSPs prepared by teachers to support children with disability in the school system. This study investigated the application of the BSP‐QEII to the assessment of BSPs for adults with ID in community support services. Method The inter‐rater reliability of the BSP‐QEII was assessed. The utility of the BPS‐QEII was then investigated with reference to a time series study of matched pairs of BSPs, developed for the same clients over a period of approximately 3 years. Differences in plan quality measured across a number of service and systemic variables were also investigated. Results The BSP‐QEII was found to have good inter‐rater reliability and good utility for audit purposes. It was able to discriminate changes in plan quality over time. Differences in plan quality were also evident across different service types, where specialist staff had or had not been involved, and in some instances where a statutory format for the plan had or had not been used. There were no differences between plans developed by government and community sector agencies, nor were there any regional differences across the jurisdiction. Conclusions The BSP‐QEII could usefully be adopted as an audit tool for measuring the quality of BSPs for adults with ID. In addition to being used for research and administrative auditing, the principles underpinning the BSP‐QEII could also be useful to guide policy and educational activities for staff in community based services for adults with ID.